THE ROLE OF DEMAND AND SUPPLY OF INVESTMENTS IN THE WORLD ECONOMY - kizi, Tugizova Malika Sokhib (Research Parks Publishers, 2023)
In the world economy, there is a trend of imbalance between demand and supply of investments. Today, we are witnessing the flow of investments from developed countries to the economies of developing countries. As a result, the share of direct investments in the economy of developing countries is increasing sharply.